Fostering Students’ Well-Being: The Mediating Role of Teacher Interpersonal Behavior and Student-Teacher Relationships - Zheng, Fang (Frontiers in Psychology, 2022)
Well-being has become extensively viewed as apprehension for administrations in the last decades and schools have been progressively realized as locations for encouraging well-being which is a considerable development in inquiries on mediations connected to learner well-being. In this way, the function of teachers has got specific consideration regarding students’ well-being, given the merits of teacher-student interactions. High-quality educator-learner relationships offer a support base for long-term learners’ education. Educator interpersonal behavior that makes learners feel supported and cared for is known as emotional support. These behaviors can help learners’ emotional and social needs; meet learners’ families, and being available when learners need additional help. This review attempts to consider the eminence of teacher interpersonal behavior and learner-teacher relations in the classroom and indeed illustrate their relationship and influence on students’ well-being. As a final point, this review can provide suggestions and recommendations for language teaching participants in the scholastic context.